Organizations and policies of non formal education - Eduard Angelo Bendrath
From a public policy centric view of education, this text provides a conceptual discussion of the influence of international organizations in formal models and non-formal education. The participation of financial agencies and UNESCO in the implementation of reforms and programs in developing countries is discussed, with the main discussion of the implementation in Brazil Open School Program of the Federal Government in partnership with UNESCO. This program aims at the inclusion of communities in schools through non-formal education, offering the possibility of access to cultural goods, professional, sports and health. It is concluded that the non-formal education is seen as a growing field, with special attention of international organizations, supported mainly by complementary actions of human formation.